GSLIB : geostatistical software library and user's guide - Deutsch, Clayton V.; Journel, A. G. (New York : Oxford University Press, 1998)
Thirty-seven programs that summarize data with histograms and other graphics, calculate measures of spatial continuity, provide smooth least-squares-type maps, and perform stochastic spatial simulation.
Title from disc label.
Includes Index.
Geoscientists.
System requirements: IBM-compatible PC; FORTRAN compiler (level 77 or higher); CD-ROM drive.
Keywords: Geology -- Statistical methods -- Software